Clusters and coherent voids in particle-laden wake flow. (August 2021) - Shi, Zhaoyu; Jiang, Fengjian; Zhao, Lihao; Andersson, Helge I
Highlights: Coherent voids are found encompassing each Kármán vortex cell. Particle clusters at the upstream of each void form the peculiar smooth edges. Deceleration history along particle trajectories relates to the smooth edge. Trajectories at one side are deflected by a vortex cell shed from the opposite side. Particles at two sides of the cylinder are affected differently by the same vortices. Graphical abstract: Abstract: Inertial point particles suspended in a two-dimensional unsteady circular cylinder flow at R e = 100 are studied by one-way coupled three-dimensional numerical simulations. The striking clustering pattern in the near-wake is strongly correlated with the periodically shed Kármán vortex cells. The particles are expelled from the vortex cores due to the centrifugal mechanism and coherent voids encompassing the local Kármán cells are therefore observed. The particle clustering at the upstream side of each void hole form a smooth edge, where the particle velocity magnitude is consistently lower than at the downstream edge of the voids. The trajectories of these particles originate from the side of the cylinder where the sign of vorticity is opposite to that of the vortex encompassed by the corresponding void hole. The particles are seen to decelerate along a substantial part of their trajectories. Particle inertia is parameterized by means of a Stokes number S k and smooth edges around the void holes still exist when S k is increased, although their formation is delayed due to larger inertia. Increasing inertia contributes to a decoupling of the particle acceleration from the slip velocity, which almost coincided at S k = 1 .